PENERAPAN SIKLUS PDCA PADA CV. DELIMA DENGAN ALAT BANTU SEVEN TOOLS - William Sutjipto; Stefanus Budy Widjaja S.; Antonius Budhiman Setyawan (CALYPTRA, 2018)
Based on the observation, it can be seen that the problem being faced by CV. Delima is the number of defective products that were produced during the production process of marie wijen Sriti in August 2017 has 13.53% of defective products, while the company has a defective tolerance limit of 10%. And the absence of clear working standards that cause the range of disability too far. Therefore, this study aims to determine whether the use of PDCA quality control with the seven tools can minimize the production defects in the CV. Delima.Quality control analysis uses PDCA with seventools, capability process, and FMEA. The tools will be used to find the production process error and also fix it so that the defect can decrease at CV. Delima. The results of capability process analysis show that the production process run by CV. Delima is not good and also the control chart shows that the company's production activities are out of control. Can be seen on the control chart there are several points that exceeds the upper and lower limits. From the analysis of cause-effect diagrams, it can be seen that the factors causing defects in products come from human factors, materials, methods, and machinery so that companies can take corrective action to overcome these problems. The results showed that the problem of production process in CV. Delima can be repaired and can minimize the production defects by using PDCA approach with seven tools tool. In addition, the percentage of marie wijen Sriti's production defects percentage decreased by 6.47%.